(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
In recent years, Cognitive Behavioural Therapy (CBT) has come to be seen as the holy grail to the nation’s mental health problems, with its results being offered up as ’scientifically proven’. Over fifty years ago, Heidegger linked art with a different kind of truth to that of science, and Gadamer continued Heidegger’s attempt at the recovery of the question of the truth of art. Key to Gadamer’s philosophy is his recognition of the element of free play within art and play as self-presentation. I argue that it is through the dynamic, play-ful art of therapy, free from set directions and goals, that we can be challenged to expand our thinking and achieve greater well-being.